2015
DOI: 10.1111/hequ.12063
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Passage of Time on Alumni Recall of ‘Student Experience’

Abstract: ‘Student experience’ has become a popular term with higher education managers but is theoretically under‐developed. This paper conceptualises student experience as a construction from memory and advances previous discussion within the higher education sector by distinguishing between recalled academic and social experience. The results of a predominantly quantitative survey of 883 alumni indicated that recalled academic experience had greater effect on subsequent loyalty attitudes and behaviours than recalled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
16
0
1
Order By: Relevance
“…Previous research has examined some of the reasons why alumni do or do not feel involved with the institution from which they have graduated. Former educational experiences and personal benefits (Thoits and Hewitt 2001), and in line with ideas from SET (Kelly and Thibaut 1959), the quality of students' former relationships with their educational faculty and staff (Koenig-Lewis et al 2016) have been found to be indicative of future alumni loyalty. The findings of this study add that in order to establish alumni loyalty, one should also focus on relationship quality dimensions, such as students' affective commitment and trust…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous research has examined some of the reasons why alumni do or do not feel involved with the institution from which they have graduated. Former educational experiences and personal benefits (Thoits and Hewitt 2001), and in line with ideas from SET (Kelly and Thibaut 1959), the quality of students' former relationships with their educational faculty and staff (Koenig-Lewis et al 2016) have been found to be indicative of future alumni loyalty. The findings of this study add that in order to establish alumni loyalty, one should also focus on relationship quality dimensions, such as students' affective commitment and trust…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the importance of alumni has long been recognized (Newman and Petrosko 2011). Much of the previous literature on alumni loyalty has been based on studies from the US, with a focus on monetary contributions (Guzman 2015;Koenig-Lewis et al 2016) such as donations and buying the universities' merchandise. While US-based alumni often automatically become alumni association members, in European countries such as the Netherlands, Belgium, and Germany, this practice is not common.…”
Section: Introductionmentioning
confidence: 99%
“…In other word, students' experience in the university is the best platform to reveal the intention of the future alumni involvement and alumni loyalty. Students' experience became a popular term among the higher educational managers but is still theoretically under-developed [7]. Alumni who enjoyed their students' experience gave positive feedback to people in their networks, acted as role models for the current students, shared their skills and experiences, and advised the program of the alma mater [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, students' experience has a major impact on feelings and opinions towards the institution when they become the alumni [4,5]. Previous authors claimed that students' experience became a popular variable among the higher educational managers but is still theoretically under-developed [6], thus the influence of students' experience should be examined particularly on the contribution of alumni giving.…”
Section: Literature Review 21 Students' Experiencementioning
confidence: 99%